2022
DOI: 10.1177/10499091221100501
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Survival Time in Advanced Lung Cancer: A Retrospective Study in Home-Based Palliative Care Unit

Abstract: Background: There is a large group of patients suffering from lung cancer and receiving home hospice care in China. However, little is known about the prediction of their survival time. The purpose of this study was to determine whether quality of life independently predicts survival among advanced lung cancer survivors who are receiving home-based palliative care. Methods: In this retrospective study, we analyzed data from 937 advanced lung cancer patients who had received home-based palliative care between M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Patients diagnosed with advanced lung cancer face a challenging prognosis characterized by a high likelihood of recurrence and persistent health threats like dyspnea. These factors exacerbate the experience of anticipatory grief, amplifying its impact on patients' emotional well‐being (Cui et al., 2023 ). Anticipatory grief contributes to a gradual decline in patients' physical condition, serving as an early indicator of illness progression.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed with advanced lung cancer face a challenging prognosis characterized by a high likelihood of recurrence and persistent health threats like dyspnea. These factors exacerbate the experience of anticipatory grief, amplifying its impact on patients' emotional well‐being (Cui et al., 2023 ). Anticipatory grief contributes to a gradual decline in patients' physical condition, serving as an early indicator of illness progression.…”
Section: Discussionmentioning
confidence: 99%
“…Lengthy cancer experience and anticancer treatments make patients experience a wide range of problems, and symptoms and side effects are widespread and often demoralizing (Candido et al, 2017; Galiano et al, 2022). Therefore, the fundamental challenge at present is to provide care for advanced cancer patients to improve their quality of life while simultaneously extending survival (Cui et al, 2023; Malhotra et al, 2017). Previous studies have shown growth in negative emotions of advanced patients with greater proximity to death (Alam et al, 2020; Lo et al, 2010); approximately 20%–65% of patients are subjected to multiple negative experiences at the end of their lives (Bail et al, 2018).…”
mentioning
confidence: 99%